1998
DOI: 10.1038/sj.onc.1202258
|View full text |Cite
|
Sign up to set email alerts
|

Novel regions of allelic deletion on chromosome 18p in tumors of the lung, brain and breast

Abstract: Lung cancer is now the number one cause of cancer death for both men and women. An age-adjusted analysis over the past 25 years shows that in women specifically, lung cancer incidence is on the rise. It is estimated that 10-20 genetic events including the alteration of oncogenes and tumor suppressor genes will have occurred by the time a lung tumor becomes clinically evident. In an effort to identify regions containing novel cancer genes, chromosome 18p11, a band not previously implicated in disease, was exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
73
2

Year Published

2000
2000
2007
2007

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(80 citation statements)
references
References 16 publications
5
73
2
Order By: Relevance
“…DAL-1 originally was implicated in the tumorigenesis of nonsmall cell lung carcinoma and subsequently has been associated with additional malignancies, including glial tumors, meningiomas, and breast carcinoma. 21,[32][33][34] Recently, Singh et al 20 used both FISH and immunohistochemistry to evaluate 27 ependymomas for NF2/merlin and DAL-1/DAL-1 at the DNA and protein levels, respectively. They found NF2/merlin losses limited to spinal ependymomas, whereas the majority of DAL-1/DAL-1 losses were detected in intracranial lesions.…”
Section: Radiologic Featuresmentioning
confidence: 99%
See 1 more Smart Citation
“…DAL-1 originally was implicated in the tumorigenesis of nonsmall cell lung carcinoma and subsequently has been associated with additional malignancies, including glial tumors, meningiomas, and breast carcinoma. 21,[32][33][34] Recently, Singh et al 20 used both FISH and immunohistochemistry to evaluate 27 ependymomas for NF2/merlin and DAL-1/DAL-1 at the DNA and protein levels, respectively. They found NF2/merlin losses limited to spinal ependymomas, whereas the majority of DAL-1/DAL-1 losses were detected in intracranial lesions.…”
Section: Radiologic Featuresmentioning
confidence: 99%
“…In a recent study by Singh et al, NF2 and DAL-1, two members of the protein 4.1 superfamily, were implicated in the pathogenesis of ependymomas. 20 Deletions/loss of NF2 (22q12) were encountered primarily in spinal ependymomas, whereas loss of DAL-1 (differentially expressed in adenocarcinoma of the lung), a related tumor suppressor gene on chromosome 18p11.3, 21,22 was more frequent in intracranial examples, including several pediatric tumors. 20 Here, we report the clinicopathologic and radiologic features, treatment, and outcome of 10 children with CCE.…”
mentioning
confidence: 99%
“…In colorectal and head and neck carcinomas, loss of 18q represents a poor prognostic marker (Jernvall et al, 1999;Pearlstein et al, 1998). In addition, the 18p11 region has been reported to contain at least two potential tumor suppressor genes implicated in lung, brain and possibly in breast cancer (Tran et al, 1998).…”
Section: Fibrolamellar Carcinomamentioning
confidence: 99%
“…Protein 4.1B is a brain-enriched ortholog of 4.1R that localizes to points of cell-cell contact at the plasma membrane (Peters et al, 1998;Parra et al, 2000). Several studies have indicated that 4.1B expression is lost or reduced in numerous malignant and benign tumors, including 54% of nonsmall cell lung carcinomas (NSCLC) (Tran et al, 1999). 4.1B is also reduced in 60% of sporadic meningiomas and 30% of ependymomas (Gutmann et al, 2000;Singh et al, 2002).…”
Section: Introductionmentioning
confidence: 99%